A Rare Case of Anterior Wall Combined With Inferior Wall Wellens Syndrome - Lei Zhang (Annals of Noninvasive Electrocardiology)
ABSTRACT This article describes a woman who presented to the hospital with recurrent chest pain. The electrocardiogram revealed positive and negative biphasic T waves in the anterior and inferior leads, which subsequently deepened. Upon recurrence of chest pain, the T waves reverted to upright. Coronary angiography indicated the presence of three‐vessel coronary artery disease. The occurrence of Wellens' T wave sign in the precordial leads frequently suggests left anterior descending artery disease, while the presence of positive and negative biphasic T waves in the inferior wall leads may also indicate lesions in the right coronary artery or left circumflex artery.